Risk factors for infection in patients with a failed kidney allograft on immunosuppressive medications - Ogawa, Lauren; Beaird, Omer E.; Schaenman, Joanna M. (Frontiers in Nephrology, 2023)
Patients with a failing kidney allograft are often continued on immunosuppression (IS) to preserve residual kidney function and prevent allosensitization. It has been previously accepted that maintaining patients on immunosuppressive therapy results in an increased risk for infection, hospitalization, and mortality. However, as management of IS in patients with a failed kidney allograft continues to evolve, it is important to review the data regarding associations between infection and specific immunosuppression regimens. We present a review of the literature of failed kidney allograft management and infectious risk, and discuss practices for infection prevention. Fifteen studies were identified, published from 1995 to 2022, that investigated the experience of patients with failed allograft and infection. Infection was most commonly documented as a general event, but when specified, included Candida, Mycobacterium tuberculosis, and Aspergillus. In addition, the definition of reduced ‘IS” varied from decreased doses of a triple drug regimen to monotherapy, while others did not specify which medications patients were receiving. Despite attempts at lowering net immunosuppression, patients with failed allografts remain at risk for opportunistic and non-opportunistic infections. While opportunistic infections secondary to IS are expected, somewhat surprisingly it appears that the greatest risk for infection may be related to complications of dialysis. Therefore, mitigating strategies such as planning for AV fistula over hemodialysis catheter placement may reduce infection risk. Additional studies are needed to provide more information regarding types and timing of infection in the setting of a failed kidney allograft. In addition, more data is needed regarding specific medications, doses, and timing of taper of IS in order to guide future patient management and inform strategies for infection surveillance and prophylaxis.